Impact of export duties on the Russian wheat market - S. K. Seitov (Аграрная наука Евро-Северо-Востока)
The aim of the research is to assess the impact of the introduction of export duties on changes in the Russian wheat market situation. The work examines the mechanism of wheat export regulation in Russia in current conditions, and also identifies its shortcomings and proposes the ways to eliminate them. The methodology of the research is based on the theory of industry markets, including the analysis of the effects of export restrictions. The study includes the period of 2017-2021. The paper shows that losses of domestic wheat producers due to export duty will exceed $ 1 billion on an annual basis since June 02, 2021. The consumer gains will reach US$ 10 million, and state budget revenues will reach US$ 10 million. The government revenues from the customs duty would be US$ 1.4 billion. The net result of Russia from the introduction of the export duty will be negative, amounting to – $ 400 million. Wheat export in Russia should not be severely restricted to prevent domestic price increases. Despite the imposed export duties, producer prices for wheat raise significantly: in August 2021 the price was $174.3 per 1 ton, in November 2021 it was $205.8. The author proposes to abolish export restrictions and focus policy measures on improving the transport system, market, information infrastructure and the spread of digital technologies in grain production, storage and transportation. The economic characteristics of the effectiveness of tariff measures can be of great value to government authorities, agricultural producers and researchers. They make it possible to improve the strategy of state export regulation in accordance with the tasks of development and the needs of society and the economy.